Two strings to one bow? Article 47 of the EU charter of fundamental rights in the EU competition case law: between procedural and substantive fairness - Giulia gentile (Market and Competition Law Review)
In recent years, the EU competition framework has been under strain because of the increasing market interconnectivity. Criticisms have raised regarding the EU competition enforcement model. In response, institutional debate and measures have focused on the enhancement of fairness in this area of EU law. Following the entry into force of the Lisbon Treaty, another source of ‘fairness’ in the enforcement of EU competition law is the EU Charter of Fundamental Rights. Article 47 of the EU Charter is the most invoked provision in the context of EU competition litigation. Considered to reaffirm the EU general principle of effective judicial protection, this article constitutionalises the right to an effective remedy and to a fair trial. Although the existing literature has highlighted the overall influence of fundamental rights in the enforcement of competition law, the contribution of Article 47 Charter, as interpreted by the Court of Justice of the European Union, in enhancing fairness in EU competition policies remains, so far, underexplored. The current paper aims to fill this gap in the literature by offering a threefold input. First, the paper situates the discussion on fairness in EU competition law in the broader philosophical debate regarding various conception(s) of fairness. Second, the paper analyses the case law of the EU Court of Justice on Article 47 of the EU Charter in EU competition litigation. Finally, the paper discusses what kind of ‘fairness’ Article 47 strengthens in the area of EU competition law enforcement.